Characteristics of the organizational and managerial activity of the fitness club director - Svitlana Stadnyk (Kharkiv State Academy of Physical Culture, 2017)
Purpose: describe the organizational and managerial activities of the fitness club director. Material & Methods: analysis of literary sources; analysis of documents; system analysis; survey (questionnaire) methods of mathematical statistics. The study was conducted on the basis of 12 fitness clubs in Kharkiv. Respondents were 12 directors, managers of fitness clubs. Results: the obtained results of the study made it possible to reveal the levels of management of the fitness club activities, structural divisions and links, their functions, management ties. From the perspective of an integrated approach, the activity of the director of the fitness club on the complexity of the tasks to be solved. Conclusion: optimal organizational structure of management of fitness clubs is defined, includes the following functional blocks: fitness staff service personnel technical staff and administration. It is determined that the financial and economic activities of the fitness club and the continuous improvement of their professional activities are the most difficult tasks in the activity of the director and manager of the fitness club.